"Strategies for the implementation of digital competences in teachers of professionaltechnical universities: experience and perspectives" - Drahun, V. (Problems of Engineer-Pedagogical Education, 2024)
This article is a survey work to determine the state of research on the problem of the implementation of digital competences among teachers of professional-technical universities. The article provides a rationale for the need to introduce digital competencies of teachers due to their significant impact on modern education and the economy. An overview of some implementations of the development of digital competence of teachers is also given. At the moment, they are more focused on the following areas: professional development programs and trainings, creation of digital educational resources, use of online platforms for learning, development of own skills, support from the management of the institution, involvement in professional communities. Separately, the article presents the prospects for further development. These can be focused around: integration with artificial intelligence, gamification, work on the spread of digital literacy and development of critical thinking, integration of mobile/cell phones and pocket computers in education, development of skills for managing large volumes of data and the application of blended learning technology. Reports of the European Commission, as well as political actions regarding education and society, also point to the need to introduce digital competences among teachers of professional-technical universities. The success of the digital transformation requires actions not only from teachers, it must be a decision of the whole society that involves political reforms, improving the business environment, creating incentives and increasing investments in digital technologies, skills and infrastructures. And the result of the success of the digital transformation may be the growth of the economy and the well-being of society. Therefore, it is assumed that the presence of digital competences among teachers of professional-technical universities will be important for the development of the country and society as a whole. Because of this, there is a need for further research into ways of implementing digital competencies among teachers of vocational and technical institutions, as well as creating an optimal implementation strategy and developing a technological solution for student training.